(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study aimed to examine the Effect of the Listen-read-discus (LRD) strategy on the students of eighth stage in basic education schools in Kurdish literature subject. The research adapt the experimental method that used to evaluate the achievement of two equal groups chosen from different schools.The researchers conducted two schools intentionally from west department of education in Duhok city.Two Groups had been chosen randomly, group (A) consists of 21 students from Hajar Mukirian school for experiment group and group (C) consists of 22 students from Aland school for the control group. The researchers ensured equivalence between the two groups in some relevant variables. To achieve the aim of the study an assessment has been conducted. The assessment consists of 35 items 25 items were multiple choices and 10 were true/ false. After applying the experimental assessment on the researcher’s sample data has been found and analysis statistically by using (t.test) experimental Design on two separated groups uneqlized in number, the results in the study showed that there is differences statistically between the two groups in the average score on the grades of the students studied Kurdish literature adopted (LRD) strategy and the average score of students grades studied the same subject in common method. In conclusion, using LRD strategy has a positive effect on students’ grades accordingly; the researchers conclude some suggestions and recommendations.